Intercompany training as production pedagogical process - Evgeny A. Korchagin; Rais S. Safin; Adelya I. Tuyusheva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article explains the corporate training as a coordinated interaction of educational and industrial processes in the preparation of in-demand professionals. This interaction is based on the unity of the three methodological bases: the axiological (priority of professional and industrial values and goals within the professional development of the individual student), ontological (the integration of science, education and production), technological (scientific organization of labor, organization and implementation of professional activity). These fundamentals determine the methodological approaches to the corporate training of staff. On the part of the production process such approaches being: compliance with the law of the workforce and the nature of and technology; The law of change of work; the law of the division of labor; the strategy (concept) of development of production technology aimed at optimizing the production process, the quality of products, reduce its production costs. From the pedagogical process - the system, the activity, andragogical, student-centered, qualification, resource approaches.